China-Malaysia Relations: The Three Dilemmas of Malaysian Chinese - Chan, Xin Ying (2017)
As Malaysia’s trade and investment with China grows a new dimension has emerged in the relationship between Malaysia, China, and the local ethnic Chinese community. Malaysian Chinese have to carefully deal with the political, social and economic repercussions of this triple dilemma.